Factors influencing the guest-host knowledge transfer for pro-poor tourism in China’s western ethnic-minority areas - Jin Wu; Shiyi Tang; Rui Zhang (PLoS ONE, 2025)
The crucial transfer of knowledge through pro-poor tourism enables poor people to enhance their own endogenous-development dynamics. However, it is difficult to use existing knowledge transfer theories to explain the behavior of ethnic-minority villagers in western China, due to low levels of education and smallholder household-based tourism operations. The present study uses MOA theory to examine the influence of motivation, opportunity, ability, and trust on the guest–host transfer of knowledge in ethnic-minority villages in western China. Here, knowledge transfer opportunities are shown to be the main driver of the MOA framework, positively affecting the knowledge transfer effect. Knowledge transfer motivation and knowledge absorptive capacity have an indirect, positive impact on knowledge transfer opportunities. Although local people have a high level of trust in external knowledge sources, trust does not have significant moderating effect between knowledge transfer opportunities and effects. These findings can be used to strengthen the transfer of valuable knowledge to villagers and to cultivate rural tourism talents.